Utilization of Baion Plants Pandanus Tectorius to Increase Economic Value and Competitiveness of Local MSMEs - Siallagan, Dahlia Nopelina; Simangunsong, Rini T; Simatupang, Lambok; Gaol, Jack Tri Okto Lumban (Journal La Sociale, 2025)
The Baion plant (Pandanus tectorius) is known as a thriving plant and as a natural resource that has many benefits. People in various regions, including Humbang Hasundutan Regency, have used these plant parts for various purposes, such as handicraft raw materials, food, and cultural products. However, maximum utilization is still not fully realized, so further research is needed to explore this potential. This effort is expected to be a solution to increase local MSME income, reduce dependence on imported materials, and preserve local wisdom. The purpose of this research is to explore the potential of Baion plants in supporting the development of MSMEs, as well as identify factors that affect the successful implementation of the use of Baion plants. This research method uses qualitative and quantitative approaches through surveys, product manufacturing experiments, and MSME training. SWOT analysis is used to evaluate market opportunities, while organoleptic tests are applied to Baion-based food products. The survey method is used to collect preliminary data from respondents, either through questionnaires or interviews, to understand market preferences and needs. On the other hand, product manufacturing experiments are carried out to evaluate variations in formulas and production methods, especially in Baion-based food products, through organoleptic tests to assess sensory quality (taste, aroma, texture, and appearance). In addition, MSME training is held to improve the ability of producers in product development and marketing. In evaluating market potential, a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis is carried out which functions to find out the strengths, weaknesses, opportunities, and threats of a business.